The government spending multiplier, fiscal stress, and the zero lower bound - Felix Strobel (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
The recent sovereign debt crisis in the Eurozone was characterized by a monetary policy, which has been constrained by the zero lower bound (ZLB) on nominal interest rates, and several countries, which faced high risk spreads on their sovereign bonds. How is the government spending multiplier affected by such an economic environment? While prominent results in the academic literature point to high government spending multipliers at the ZLB, higher public indebtedness is often associated with small government spending multipliers. I develop a DSGE model with leverage constrained banks that captures both features of this economic environment, the ZLB and fiscal stress. In this model, I analyze the effects of government spending shocks. I find that not only are multipliers large at the ZLB, the presence of fiscal stress can even increase their size. For longer durations of the ZLB, multipliers in this model can be considerably larger than one.
Keywords: E32; E44; E62; H30; H60; 330; Government spending multiplier; Fiscal stress; Zero lower bound; Financial frictions